Community of Bivalves in Mangrove Area Mesjid Lama Village, Talawi Sub-district Batubara Regency, Sumatera Utara Province - El Fajri, Nur; Putra, Ridwan Manda; ', Susanti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in Maret 2013. This study aims to understandbivalves communities in mangrove area Mesjid Lama village. The method used in this research is the case study method. This research executed at three perception station with different condition.Data analysis using diversity index (H'), dominance index (C) and equitability index (E) and the value of bivalves abundance. Observations found one families are Corbicullidae.In the surface, the bivalves abundance was ranged from 25.000-51.667ind/ha.; mangrove density 600-1.522trees/ha; diversity index 0,8768 - 0,9446; dominance index 0,558–0,5378; equitability index 0,9142–0,9446; temperatures ranging 29– 31⁰ C; water pH 8; lan pH 7,51-7,62 ; salinity 15-25 o/oo; organic material 34,7-55,1 % and sediment fraction 66,6-75,9 %..Keyword : Community of fish, water quality, activities, Singkarak Lake.